AB1071 The Use of Visual Analogue Scale in Rheumatic Disease: Validation of an Electronic Version. (10th June 2014) - Cunha-Miranda, L.; Barcelos, F.; Miguel, C.; Silva, C.; Santos, H.; Fernandes, S.; Borges, J.; Trinca, R.; Vicente, V.; Aguiar, P.
Abstract : Background: VAS scales are very useful and easy to perform scales that rheumatologists use on a daily basis. There are several ways to perform this evaluation, on paper through a ruler that includes a slider indicator among others. With the use of more electronic patient's records it is useful to determine if the use of a computer assisted VAS could perform the same as the paper. Objectives: To evaluate and validate an electronic based VAS in a touch-screen platform. Methods: Patients followed in our biologic clinic were evaluated with a paper version of several visual analogue scale (disease activity, pain intensity, back pain in the night, back pain anytime and how the disease disturbs) and after with the electronic version according to their diagnosis. The touch-screen was specially developed for our patients, integrating software that recognized the patient by disease through a bar code and presented the questionnaires according to the disease. Concordance between paper rand touch-screen questionnaire was done through Intraclass Correlation Coefficients. Internal consistency was evaluated by Cronbach's alpha coefficient. Results: A total of 88 patients were included in the global disease scale (80.7% rheumatoid arthritis and 19, 3% psoriatic arthritis) 85.2% were female, mean age was 54.34±11.05 years and mean disease duration was 11.83±9.32 years. Several other VAS used in spondyloarthropathies was compared in a group of 56 patients the majority were man (58.9%), 30.4% had psoriatic arthritis, 69, 6% had ankylosing spondylitis mean age was 46.69±11.78 years and mean disease duration was 10.4±8.77years. Conclusions: We found no relevant difference between paper and touch-screen version of all the used VAS scales, with high correlation coefficients validating this platform. This is a useful instrument in our clinical practice, and could be a valid alternative to VAS on paper or rulers. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5384